Psychosocial dimensions of access and their association with contraceptive use and intention to use - Lonkila Moussa Zan; Clémentine Rossier (BMC, 2024)
Abstract Background Several studies suggest that psychosocial accessibility appears to be the key remaining hurdle to contraceptive use when issues of geographic and financial accessibility have been resolved. To date, the literature has considered various dimensions of psychosocial accessibility, which are not well measured by the two main sources of contraceptive data (DHS and PMA2020). In a previous paper, we have designed a framework that outlines four subdimensions of cognitive and psychosocial access and their theoretical relationship to contraceptive use and intention to use. This paper aims to study the associations between the four dimensions of access to contraception with the contraceptive use and intention to use. It also aims to explore the mediation effect of these four dimensions of access in the relationships between classical individual characteristics and contraceptive use and intention to use. Methods The data we used came from the 6th round of the PMA2020 survey in Burkina Faso in 2018-19. This survey included 2,763 households (98.4% response rate) and 3329 women (97.7% response rate). In addition to PMA's core questions, this survey collected data on psychosocial accessibility. Each group of questions was added to address one dimension. We use a multilevel generalized structural equation and mediation modeling to test the associations between psychosocial accessibility and contraceptive use while controlling for some individual and contextual characteristics. Results Approval, contraceptive knowledge, and agency were associated with contraceptive use, while fears of side effects were not. Approval and agency explain part of the effects of education and parity on contraceptive use. Exposure to family planning messages had a positive impact on women's contraceptive agency. Conclusion FP messages can help enhance women's contraceptive agency, and then, contraceptive use, regardless of age and parity. The analysis highlights the mediator effects of contraceptive approval and agency on the association between parity and education with contraceptive use.